Implementasi Kebijakan Program Desa Mandiri Anggur Merah ( studi kasus di Desa Lukukamaru Kecamatan Kota Waingapu Kabupaten Sumba Timur Provinsi Nusa Tenggara Timur) - Rambu Kahi Bili, Eunike Cahya Pratama; Pascarani, Ni Nyoman Dewi; Yudharta, I Putu Dharmanu (CITIZEN CHARTER, 2017)
ABSTRACT Population growth from many years carries some effects in all aspects like education, health, economy and those are followed by problems that show up just like the problem that is caused by population growth which is the poverty problem. Poverty happens in every region in Indonesia especially in East Nusa Tenggara that even becomes the third poorest Province in Indonesia. East Nusa Tenggara Province Government takes a responsibility to solve poverty problem in their area with making an Anggur Merah Autonomic Village Program Policy Implementation which is targetting all poor villages in East Nusa Tenggara. This study uses a descriptive qualitative research methodology. In collecting data, the writer does a direct observation on the field to collect all primary data that is related with doing documentation study to collect the secondary data. Besides, the writer uses interview technique directly and indirectly that are related with this topic of research. The summary of this research is an Anggur Merah Autonomic Village Program Policy Implementation in Lukukamaru village since 2011 can be felt by the group society that has given donations which is consisted of 10 groups in first shift and 7 groups in second shift. In the implementation of this program, there is still a term disorder with a regulation that is agreed. Obstacles or chalenges that must be solved are the Lukukamaru peopleâ€™s concern, a continuity of evaluation by the government in this village and supporting infrastructurs improvements of this program. Â Keywords: public policy, public policy implementation, poverty